Nail changes in pemphigus and bullous pemphigoid: A single-center study in China - Cao, Shan; Cui, Xiaochen; Li, Jianke; Pan, Futang; Yan, Xiaoxiao; Yang, Qing; Chen, Mingfei; Zhou, Shengji; Du, Donghong; Wang, Weiwei; Sun, Yuanhang; Shi, Zhongxiang; et al. (Frontiers in Medicine, 2022)
Common autoimmune bullous diseases (AIBDs) include pemphigus and bullous pemphigoid (BP), which are primarily caused by IgG autoantibodies against the structural proteins of desmosomes at the cell–cell junction and hemidesmosomes at the epidermal–dermal junction. Few studies have assessed nail changes in patients with pemphigus or BP. In the present study, we collected the clinical data of 191 patients with AIBDs (108 patients with pemphigus and 83 patients with BP) and 200 control subjects. Nail changes were observed in 77.0% (147/191), 77.8% (84/108), and 75.9% (63/83) of patients with AIBDs, pemphigus, and BP, respectively, and 14.5% (29/200) of control subjects. Beau's lines and paronychia were the most common nail involvement, observed in 22.5% (43/191) and 22.5% (43/191) of patients with AIBDs, 25.0% (27/108) and 25.9% (28/108) of patients with pemphigus, 19.3% (16/83) and 18.1% (15/83) of patients with BP, respectively. The autoimmune bullous skin disorder intensity score (ABSIS) and the onset time of patients with pemphigus or BP with nail changes were different. Onychomycosis accounted for 21.5% (41/191) of all patients with AIBDs. The ABSIS was correlated with nail involvement in patients with BP (r = 0.46, p < 0.001), and weakly correlated with nail involvement in patients with AIBDs (r = 0.37, p < 0.001), pemphigus (r = 0.29, p = 0.009), and pemphigus vulgaris (PV; r = 0.35, p = 0.008). No correlation was observed between nail involvement and disease antibody titers. In conclusion, nail changes are frequently observed in patients with pemphigus and BP. The type and onset time of nail changes may indicate the severity of pemphigus and BP, which warrants the attention of dermatologists.